2008
DOI: 10.1007/s10800-008-9655-7
|View full text |Cite
|
Sign up to set email alerts
|

Properties and mechanism of solar absorber CdTe thin film synthesis by unipolar galvanic pulsed electrodeposition

Abstract: Electrochemical deposition of CdTe semiconductor thin films over transparent conducting glass substrates by sequential unipolar current pulses is described. The magnitude of pulsed current and pulse periodicity affects the crystalline structure, morphology, optical absorbance and composition of CdTe films. CdTe films formed under high magnitude pulsed current density *5-15 mA cm -2 are crystalline with dominant cubic structure having (111) plane oriented parallel to the substrate. Stoichiometric CdTe film grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…CdTe, a direct-band-gap material with a band gap of 1.54 eV, is another important cadmium chalcogenide than has been widely used for photovoltaic devices. In most of the reports, the electrodeposition fabrication of CdTe was conducted at a constant potential using an aqueous electrolyte with an acidic medium [61][62][63]. The following are the reactions occurring at the cathode where the CdTe is deposited [62,64,65]:…”
Section: Cdtementioning
confidence: 99%
See 2 more Smart Citations
“…CdTe, a direct-band-gap material with a band gap of 1.54 eV, is another important cadmium chalcogenide than has been widely used for photovoltaic devices. In most of the reports, the electrodeposition fabrication of CdTe was conducted at a constant potential using an aqueous electrolyte with an acidic medium [61][62][63]. The following are the reactions occurring at the cathode where the CdTe is deposited [62,64,65]:…”
Section: Cdtementioning
confidence: 99%
“…In most of the reports, the electrodeposition fabrication of CdTe was conducted at a constant potential using an aqueous electrolyte with an acidic medium [61][62][63]. The following are the reactions occurring at the cathode where the CdTe is deposited [62,64,65]:…”
Section: Cdtementioning
confidence: 99%
See 1 more Smart Citation
“…Electrodeposition under galvanostatic, potentiostatic and pulsed current techniques for the synthesis of thin films of binary semiconductors mainly, [23,24], [25], [26,27] and [28] have been widely employed in the past for the fabrication of thin film solar cells. Conventionally, the electrodeposition of semiconductor films has been carried out from aqueous or organic electrolytes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…During the cathodic scan, a current plateau that ranged from−0.7 V to −0.5 V appeared following the cathodic peak (approximately E = −0.3 V) caused by the reduction of Te (IV). Many studies [39][40][41][42] have reported that CdTe films are formed in this potential range in accordance with the following reaction: Cd 2+ + Te +2e → CdTe. Based on the above analysis, −0.6 V was selected as the deposition potential for CdTe.…”
Section: Preparation and Characterization Of Cdte/rgo/ito-to Under-mentioning
confidence: 77%